Intellectual Property: Issues of Introduction into Circulation - L. M. Kupriyanova; N. E. Sokolinskaya (Мир новой экономики, 2021)
The article discusses organisational and economical methods of implementing intellectual property into civil circulation. The introduction of intellectual property will be legal and can be used for commercial purposes in the future. The ultimate goal of commercialisation of intellectual property is to profi from scientifi, technical and innovative activities by organising the production of high-tech competitive products. It is necessary to have a qualifid team of managerscapable of developing and implementing the most optimal business strategy, within which a large number of tasks related to market research (marketing and patent research), the formation of a portfolio of intellectual property objects, the choice of economical ways of their maximum legal protection will be solved, as well as the choice and implementation of specifi ways of introducing the IPO into civil circulation, continuous monitoring on the market and, if necessary, the adoption of protective measures.